‘Break the Chains 2015’ community-based HIV prevention campaign for men who have sex with men in Switzerland: non-randomised evaluation and cost analysis - Matthias Schwenkglenks; Axel Schmidt; Kathrin Frey; Stéphanie Lociciro; Patricia Blank; Françoise Dubois-Arber; Rolf Rosenbrock; Andreas Lehner; Roger Staub; Steven Derendinger; Raphael Bize; Daniel Kübler (BMJ Open)
Objectives To study the implementation, effects and costs of Break the Chains, a community-based HIV prevention campaign for men who have sex with men (MSM) in Switzerland, from March to May 2015, which aimed to reduce early HIV transmission by promoting the campaign message to adopt short-term risk reduction followed by HIV testing.Design Non-randomised evaluation and cost analysis.Setting Gay venues in 11 of 26 cantons in Switzerland and national online media campaign.Participants MSM in online surveys (precampaign n=834, postcampaign n=688) or attending HIV testing centres (n=885); campaign managers (n=9); and campaign staff (n=38) or further intermediaries (n=80) in an online survey.Primary and secondary outcome measures The primary outcome measure was the proportion of MSM at risk of HIV acquisition or transmission who adhered to the campaign message. Secondary outcomes were postcampaign test uptake, knowledge about HIV primary infection and sense of belonging to the gay community.Results Campaign staff estimated that they contacted 17 145 MSM in 11 cantons. Among 688 respondents to the postcampaign survey, 311 (45.2%) were categorised as MSM at risk. Of 402/688 (58.5%) MSM who had heard about Break the Chains 2015, MSM categorised as being at risk were less likely to report adherence to the campaign message than MSM not at risk (adjusted OR 0.24; 95% CI 0.14 to 0.42). Twenty per cent of MSM with a defined risk of HIV acquisition or transmission who adopted risk reduction declared having done so because of the campaign. Costs for one MSM at risk to adhere to the campaign message were estimated at USD purchasing power parity 36–55. The number of HIV tests in the month after the campaign was twice the monthly average.Conclusion Break the Chains increased HIV testing, implying that community-based campaigns are useful HIV prevention strategies for MSM. Additional interventions are needed to reach MSM at the highest risk of infection more effectively.